MENGOPTIMALKAN STRATEGI PEMASARAN UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM KSPPS BMT NU KEDIRI - Agus Makinuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Increasing community participation in microfinance institutions, especially the Sharia Savings and Loans and Financing Cooperative (KSPPS) BMT NU Kediri, is a complex but crucial challenge for the sustainability and growth of these institutions. This research aims to evaluate and optimize the marketing strategy implemented by KSPPS BMT NU Kediri to increase community participation as members and customers. The research methodology involves a comprehensive case study approach, with data collection through interviews with stakeholders, surveys of members and potential members, and analysis of existing marketing strategies. This research identifies various factors that influence the community's decision to join KSPPS BMT NU Kediri, including the marketing strategies implemented and the community's response to these marketing techniques. The research results show that an integrated marketing strategy, which includes a combination of digital marketing, community-based promotions, and financial education programs, significantly increases public interest and engagement. These findings highlight the importance of a holistic and adaptive approach in designing marketing strategies that are relevant to local needs and characteristics.